Komunitas Politis: Fakta atau Hipotesa? Sebuah Pendekatan Fenomenologi Politis - Reza A.A Wattimena (Arete, 2012)
In this paper, I want to give description and analysis concerning the meaning of the term political community. This paper also can be seen as a participation in the perennial debates concerning the problem of the order in the philosophy of social sciences. I will use phenomenology as a method to approach this problem as it developed by John Drummond and Edmund Husserl. The main argument is that the political community is a social fact that develop through hypothesis, and a hyphotesis that based always on social fact. In the end, I will give my critical remarks on this argument.